Pleasure Reading, Better Understanding: A Young EFL Learner’s Journey in Digital Extensive Reading - Putri, Zalva Fajhira Shabrina; Damayanti, Ika Lestari (Universitas Muhammadiyah Yogyakarta, 2000)
Background: The struggle of a young English as a foreign language (EFL) learner in the midst of advanced technology to find pleasure and develop good comprehension in reading English materials necessitates the need to employ effective approaches in their reading experience. Objective: This study investigated the implementation of digital extensive reading (DER) with a young EFL learner in Indonesia, exploring which established principles of extensive reading (ER) by Day and Bamford (1998) could be utilized in a digital context to foster reading for pleasure and comprehension. Methods: This study employed a qualitative case study research design involving a seven-year-old young EFL learner in Indonesia. The data were obtained through multiple sources, including a learner diary, audio-recorded observations of ten DER sessions, and an interview with the learner’s father. The data were analyzed using thematic analysis, referencing Day and Bamford’s (1998) top ten principles of ER. Findings: The findings revealed that eight ER principles could be effectively implemented in the young EFL learner’s DER experience, showcasing the learner’s positive attitudes towards reading and enhanced reading comprehension. Conclusion: Considering the result, the study recommends future studies to dig deeper into the effectiveness of DER across diverse learners by taking into account factors such as different ages, language proficiencies, learning styles, and technology access.